Insulin Resistance and Chronic Kidney Disease in Patients with Type 1 Diabetes Mellitus - Mihaela Vladu; Diana Clenciu; Ion Cristian Efrem; Mircea-Cătalin Forțofoiu; Anca Amzolini; Simona Tudorică Micu; Maria Moţa; Maria Forțofoiu (Journal of Nutrition and Metabolism)
Background and Aims. Diabetes mellitus (DM) is a chronic disease which can evolve towards devastating micro- and macrovascular complications. DM is the most frequent cause of chronic kidney disease (CKD). Insulin resistance plays an important role in the natural history of type 1 diabetes. The purpose of the study was to determine the prevalence of CKD in T1DM and the correlation with insulin resistance (IR) in patients with CKD. Materials and Methods. The study was conducted over a period of three years (2010–2013) and included patients with DM registered in the Clinical Centre of Diabetes, Nutrition and Metabolic Diseases of Dolj county. The study design was an epidemiological, transversal, noninterventional type. Finally, the study group included 200 subjects with type 1 DM. Insulin resistance (IR) was estimated by eGDR. The subjects with eGDR ≤ 7.5 mg/kg/min were considered with insulin resistance. Results. CKD was found in 44% of the patients. Analyzing statistically the presence of CKD, we found highly significant differences between patients with CKD and those without CKD regarding age and sex of the patients, the duration of diabetes, glycosylated hemoglobin (HbA1c), the estimated glucose disposal rate (eGDR), and the presence of hypertension, dyslipidemia, and hyperuricaemia. In patients with CKD, age and diabetes duration are significantly higher than in those who do not have this complication. CKD is more frequent in males than in females (50.9% men versus 34.5% women, p=0.022). From the elements of metabolic syndrome, high blood pressure, hyperuricemia, and dyslipidemia are significantly increased in diabetic patients with CKD. eGDR value (expressed as mg·kg−1·min−1) is lower in patients with CKD than in those without CKD (15.92 versus 6.42, p<0.001) indicating the fact that patients with CKD show higher insulin resistance than those without CKD. Conclusions. This study has shown that insulin resistance is associated with an increased risk of CKD, but, due to the cross-sectional design, the causal relationship cannot be assessed. However, the existence of this causality and the treatment benefit of insulin resistance in type 1 diabetes are issues for further discussion.